Effect of different forms of trace minerals on the performance of exotic pigs - Mishra, A; Bhattacharya, S; Samanta, G (The Indian Journal of Animal Sciences, 2005)
A feeding trial was carried out with 27 weaning (30-days-old) Large White Yorkshire piglets. The piglets were supplemented with trace minerals like copper (Cu), zinc (Zn) and manganese (Mn) in 3 conventional (T1), inorganic chelated mineral (T2) and organic chelated mineral (T3) forms respectively. A pre-weaning 30 days experimental period showed that body weight gain was highest in inorganic chelated group [T2) followed by organic chelated group (T3) and conventional group (T1) but the differences were not statistically significant (P&lt0.05). The highest feed consumption was observed in T3, followed by T1 and T2. However, superior feed efficiency was observed in T2 followed by T3 and T1 groups. The post-weaning 50 days experimental period showed that the piglets maintained superior trend of growth with chelated minerals than conventional but the differences were statistically significant (P&gt0.05). The feed efficiency ratio in postweaning period was the best in the organic chelated group (T3) followed by T2 and T1, groups.The performance index in the post-waning period was higher in organic chelated group (T3) followed by T1 and T2 groups. The overall performance of piglets for pre and post-weaning (0-90 days) expeirmentaly period showed that both inorganic and organic chelated trace minerals (T2 and T1)had superior body weight gain, better feed efficiency ratio, higher performance index and digestibility of nutrients conventional trace minerals (T1). Economic of feeding showed that highest profit was obtained with inorganic chelated group (T2) followed by organic chelate (T3) and conventional trace minerals (T1) on the performance of piglets.